Dermoid of the Nasopharynx Causing Neonatal Respiratory Distress - Manica,Denise (2013)
The dermoid is a rare and benign malformation of bigerminal origin. It is seen frequently in the neonatal period, and the clinical presentation depends on the site and on the size of the lesion, and the classical clinical picture is of a tumor derived from the naso- or oropharynx, leading to respiratory distress and/or feeding disorders. A female newborn was born cyanotic requiring intubation. The oroscopy revealed a large smooth mass. Transoral surgery was performed with successful extubation. Seven months after, there are no signs of recurrence of the lesion. This report adds another case of this rare pathology that can be life-threatening condition in the neonate. It emphasizes the importance of dermoid in the differential diagnosis of the naso- or oropharyngeal lesions, especially in neonates.